Elevated circulating lnc‐ANRIL/miR‐125a axis level predicts higher risk, more severe disease condition, and worse prognosis of sepsis. Issue 6 (21st May 2019) - Gui, Feng; Peng, Huan; Liu, Yijue
Abstract: Aim: This study aimed to investigate the correlation of lnc‐ANRIL/miR‐125a axis with risk, severity, inflammation, and prognosis of sepsis. Methods: A hundred and twenty‐six sepsis patients and 125 healthy controls were recruited, and then, blood samples were collected, and plasma was separated for lnc‐ANRIL, miR‐125a, lnc‐ANRIL/miR‐125a axis, and inflammatory cytokine level detections. In addition, basic characteristics, 28‐day mortality, and accumulating survival of sepsis patients were recorded. Results: Plasma lnc‐ANRIL expression was increased, miR‐125a expression was decreased, and lnc‐ANRIL/miR‐125a axis level was elevated in sepsis patients compared with healthy controls, and all of them had good value for predicting sepsis risk with AUCs of 0.800, 0.817, and 0.843, respectively. Lnc‐ANRIL and lnc‐ANRIL/miR‐125a axis were positively correlated with biochemical index levels including CRP and PCT levels, disease severity scale scores, and pro‐inflammatory cytokine levels in sepsis patients, while miR‐125a displayed the opposite trend. Lnc‐ANRIL and lnc‐ANRIL/miR‐125a axis expressions were elevated, while miR‐125a expression was declined in deaths compared with survivors, and all of them predicted 28‐day mortality in sepsis patients with AUCs of 0.765, 0.745, and 0.785, respectively. Subsequently, the Kaplan‐Meier analysis revealed that patients with high lnc‐ANRIL, low miR‐125a, and high lnc‐ANRIL/miR‐125a axis levels presented with worse accumulating survival. In addition, multivariate regression model analyses revealed that high plasma lnc‐ANRIL/miR‐125a axis was an independent predictive factor for both increased 28‐day mortality and worse accumulating survival. Conclusion: Circulating lnc‐ANRIL/miR‐125a axis was upregulated and could serve as a biomarker for severity, inflammation, and prognosis in sepsis patients.